PENGARUH OBJEK/DAYA TARIK, PELAYANAN, AKSESIBILTAS, DAN SARANA PRASARANA TERHADAP KEPUTUSAN WISATAWAN UNTUK BERKUNJUNG KE OBJEK WISATA PADANG SUMATERA BARAT - Nelvi Susgenti (Jurnal Pariwisata Bunda, 2020)
Tourism can not saparated from human activities especialy social activities . this research has purpose to know, 1. The effect of tourism object to tourist decision in visiting Padang West sumatera 2. The effect of services to tourist decision in visiting Padang West sumatera. 3. The effect of acesebility to tourist decision in visiting Padang West sumatera. 4. The public servives effect to tourist decision in visiting Padang West sumatera. The population from the result is all tourist which visit to Padang west sumatera, the technique sampling by using accident sampling with 400 respondens. The research instrument is arranged in questioner Likert scale model which based on free variable such as: object attraction, services, accesebility, public services and certain variable on tourist decision. From the result of research , it is found that there are the significant influences between object attraction to tourist decision in visiting Padang West sumatera . The effect of services to tourist decision in visiting Padang West sumatera. The effect of acesebility to tourist decision in visiting Padang West sumatera. 4. The public services effect to tourist decision in visiting Padang West sumatera. Based on this research that is suggest to increase tourist visiting to Padang West sumatera, there are some steps to do to run by tourism people, from government or private such as increasing object attraction,services, accesebility and public services, in order to create more satisfaction tourism.